Cognitive Scaffolding in AI-Assisted Writing: An Empirical Study of Human Creativity and Content Authenticity - Sheik Mohamed S H; M Nirmala; S Makesh (Tech : Journal of Engineering Science, 2026)
Artificial Intelligence (AI) has significantly transformed the landscape of academic and professional writing by offering intelligent support in idea generation, content organization, language refinement, and editing. AI-assisted writing tools such as ChatGPT, Gemini, Perplexity, and QuillBot are increasingly used as cognitive support systems that reduce mental effort and improve writing productivity. However, concerns regarding originality, plagiarism, misinformation, and overdependence on AI-generated content continue to raise ethical and academic challenges. The present study examines the influence of AI-assisted writing on writing cognition and content authenticity through the concept of Human–AI Synergy. The study adopted a quantitative research design using a structured questionnaire distributed among 30 respondents, including students, teachers, and content writers familiar with AI writing tools. Statistical techniques such as Percentage Analysis, Chi-Square Test, Correlation Analysis, One-Way ANOVA, and exploratory Structural Equation Modeling (SEM) were employed for data analysis. The findings reveal that AI tools positively influence writing cognition by enhancing brainstorming, idea organization, productivity, and language quality. SEM results confirmed significant relationships between Human–AI Synergy, Writing Cognition, and Content Authenticity. The study also emphasizes that while AI improves writing efficiency, human creativity, ethical judgment, and critical evaluation remain essential to ensure originality and authenticity in writing practices. The study concludes that AI should be viewed as a collaborative cognitive partner rather than a replacement for human intellectual effort. Effective integration of AI in writing requires ethical awareness, institutional guidelines, and responsible human supervision to balance technological assistance with creativity and academic integrity.